A comparison of primary and passaged chondrocytes for use in engineering the temporomandibular joint - Anderson, D.E.J.; Athanasiou, K.A.
Objective: This study examines the tissue engineering potential of passaged (P3)and primary (P0)articular chondrocytes (ACs)and costal chondrocytes (CCs)from skeletally mature goats for use in the temporomandibular joint (TMJ). Design: These four cell types were assembled into scaffoldless tissue engineered constructs and cultured for 4 wks. The constructs were then tested for cell, collagen, and glycosaminoglycan (GAG)content with biochemical assays, and collagen types I and II with enzymelinked immunosorbent assays. Constructs were also tested under tension and compression to determine biomechanical properties. Results: Both primary and passaged CC constructs had greater GAG/wet weight than AC constructs. Primary AC constructs had significantly less total collagen and contained no collagen type I. AC P3 constructs had the largest collagen I/collagen II ratio, which was also greater in passaged CC constructs relative to primary groups. Primary AC constructs were not mechanically testable, whereas passaged AC and CC constructs had significantly greater tensile properties than primary CC constructs. Conclusions: Primary CCs are considerably better than primary ACs and have potential use in tissue engineering when larger quantities of collagen type II are desired. The poor performance of the ACs, in this study, which contradicts the results seen with previous studies using immature bovine ACs, may thus be attributed to the animals' maturity. However, CC P3 cells appear particularly well suited for tissue engineering fibrocartilage of the TMJ due to the high quantity of collagen and GAG, and tensile and compressive mechanical properties.
Keywords: TISSUE ENGINEERING; ARTICULAR CHONDROCYTE; COSTAL CHONDROCYTE; CARTILAGE; FIBROCARTILAGE; MECHANICAL PROPERTIES; EXTRACELLULAR MATRIX